Problem Based Learning (PBL) to Build Literacy Skills in Students at SMAN 2 Palembang - Rini, Rizky Setya; Salsabillah, Nara Shakti; Hudaidah, Hudaidah (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
Literacy skills play an important role in students' learning success. These skills can support the competencies they have so that they can support each other if students can master literacy skills. Problem Based Learning (PBL) based learning is a learning model that can facilitate building literacy skills in students in Indonesian material during the reform era. The method used in this research was Class Action Research (PTK) or Action Research which was carried out in class XII IPA 5 SMA Negeri 2 Palembang with a total of 39 students. Research activities are carried out in two cycles consisting of planning, implementation, observation and reflection. In quantitative data collection techniques with a qualitative approach. Based on the research results, the Problem Based Learning learning model can build literacy skills in students. This was proven in cycle I that literacy skills only got a percentage of 44%, while in cycle II it increased to 90%. The conclusion from this research is that the use of the Problem Based Learning model can build literacy skills in students.